STRATEGIC COOPERATION OF SUPREME AUDIT INSTITUTIONS OF THAILAND AND TÜRKİYE FOR DIGITAL TRANSFORMATION AND INNOVATION IN PUBLIC SECTOR AUDITING - HACI ÖMER KÖSE (Sayıştay Dergisi)
Accelerating digital transformation has become a key priority for supreme audit institutions (SAIs) in order to increase their institutional capacity and to contribute more to the institutions they audit, the parliament and the public by strengthening their democratic functions. Effectively benefiting from the transformative effects of new digital technologies is a strategic priority for both the State Audit Office of Thailand (SAO) and the Turkish Court of Accounts (TCA), and they stand out among their peers with the unique systems they have developed. Also, both SAIs attach special importance to strategic cooperation to continuously improve their digital competencies and to effectively benefit from the opportunities offered by new technologies, especially big data analytics and artificial intelligence, in auditing. The study examines the successes achieved by the SAIs of Türkiye and Thailand in the field of innovation and digital transformation and the potential benefits of strategic cooperation to further advance these successes. This study is distinctive in its focus on the enhanced efficiency resulting from increased cooperation and joint action capacity among SAIs, which are responsible for promoting digital transformation and innovation not only within their own organizations but also in the institutions they audit.